ERK phosphorylation disrupts the intramolecular interaction of capicua to promote cytoplasmic translocation of capicua and tumor growth - Park, Jongmin; Park, Guk-Yeol; Lee, Jongeun; Park, Joonyoung; Kim, Soeun; Kim, Eunjeong; Park, Seung-Yeol; Yoon, Jong Hyuk; Lee, Yoontae (Frontiers in Molecular Biosciences, 2022)
Activation of receptor tyrosine kinase signaling inactivates capicua (CIC), a transcriptional repressor that functions as a tumor suppressor, via degradation and/or cytoplasmic translocation. Although CIC is known to be inactivated by phosphorylation, the mechanisms underlying the cytoplasmic translocation of CIC remain poorly understood. Therefore, we aimed to evaluate the roles of extracellular signal-regulated kinase (ERK), p90RSK, and c-SRC in the epidermal growth factor receptor (EGFR) activation-induced cytoplasmic translocation of CIC and further investigated the molecular basis for this process. We found that nuclear ERK induced the cytoplasmic translocation of CIC-S. We identified 12 serine and threonine (S/T) residues within CIC, including S173 and S301 residues that are phosphorylated by p90RSK, which contribute to the cytoplasmic translocation of CIC-S when phosphorylated. The amino-terminal (CIC-S-N) and carboxyl-terminal (CIC-S-C) regions of CIC-S were found to interact with each other to promote their nuclear localization. EGF treatment disrupted the interaction between CIC-S-N and CIC-S-C and induced their cytoplasmic translocation. Alanine substitution for the 12 S/T residues blocked the cytoplasmic translocation of CIC-S and consequently enhanced the tumor suppressor activity of CIC-S. Our study demonstrates that ERK-mediated disruption of intramolecular interaction of CIC is critical for the cytoplasmic translocation of CIC, and suggests that the nuclear retention of CIC may represent a strategy for cancer therapy.